Maeve McHugh. The Ancient Greek Farmstead. - Meens, Anna (Journal of Greek Archaeology, 2018)
While Greek farming has received plenty of scholarly attention, this is the first book-length study devoted to ancient Greek farmsteads. Given the amount of discussion about farmsteads – ranging from debating their archaeological signature to even questioning their very existence in the Greek world – it is remarkable that such a book was not written sooner. The contribution by Maeve McHugh, therefore, is very welcome because it is the first time that the ancient Greek farmstead is treated integrally, thereby tying together a very fragmented scholarly discourse.